Answer:
The answer is: " 6 " .
→ " y = 6 " .
_______________________
Explanation:
We are given the equation:
y = - x + 7 ;
We are given that: " ( 1 , y ) " ;
is a point on the graph.
So, we are asked to find the value for " y " in the given
equation when " x = 1 " .
_______________________
So, given the equation:
y = - x + 7 ;
Substitute: " 1 " for " x" ; and: "Solve for "y" :
y = - (1) + 7 ;
_______________________
y = -1 + 7 ;
y = 7 + (-1) ;
y = 7 - 1 ;
y = 6 .
_______________________
The answer is: " 6 " .
→ " y = 6 " .
_______________________
Hope this answer — and explanation — was of help!
Best wishes!
_______________________